Total oesophago‐gastric dissociation in neurologically impaired children: Laparoscopic vs robotic approach. Issue 1 (3rd December 2019) - Mattioli, Girolamo; Wong, Michela C.Y.; Angotti, Rossella; Mazzola, Cinzia; Arrigo, Serena; Gandullia, Paolo; Mancardi, Margherita; Fusi, Giulia; Messina, Mario; Zanaboni, Clelia; Razore, Barbara; Barabino, Arrigo; et al.
Abstract: Purpose: To evaluate and compare the feasibility and short‐term results of laparoscopic and robotic total oesophago‐gastric dissociation (TOGD) with a Roux‐en‐Y oesophago‐jejunostomy. Minimal invasive surgery has multiple advantages in neurologically impaired patients. Robotic approach has overcome disadvantages linked to laparoscopy, in particular, referring to the surgeon fatigue. Methods: A retrospective study comparing five laparoscopic and five robotic TOGD was conducted between February and October 2016 in Giannina Gaslini Children's Hospital and Section of Pediatric Surgery of Siena. Neurologically impaired children scheduled for TOGD were included. Age, sex, weight, symptomatology, presence of epilepsy, and preoperative X‐ray contrast were considered. Operative time, hospital stay, postoperative complications, redo surgery, nutrition rehabilitation, and X‐ray contrast study after 5 days and after 1 month from the intervention were recorded. Results: In our series, there were no intraoperative complications, no conversions to open surgery, and no vagal lesions. In two of five robotic cases, a pyloroplasty was necessary. The median operative time was statistically longer in the robotic group. One dehiscence in the robotic group was recorded, and no dumping episodes occurred. No statistical differences in terms of complications were detected. Conclusion: TOGD is feasible both with laparoscopic and robotic‐assisted surgery with similar results. Robotic approach is considered feasible. At the same time, high laparoscopic skills allow to reach the same results as robotic approach with shorter operative time.